2021 IEEE 19th International Symposium on Intelligent Systems and Informatics (SISY) 2021
DOI: 10.1109/sisy52375.2021.9582504
|View full text |Cite
|
Sign up to set email alerts
|

Inertial sensor-based outdoor terrain classification for wheeled mobile robots

Abstract: Nowadays, an increasing usage of autonomous mobile robots in outdoor applications can be noticed. Identification of the terrain type is very important for efficient navigation. In this paper, a novel method is proposed for terrain classification in the case of wheeled mobile robots. The classification algorithm uses frequency domain features, which are extracted in fixed-size windows, and Multi-Layer Perceptron (MLP) neural networks as classifiers. Data from inertial sensors were collected for different outdoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…However, the incorporated sensors are imperfect, namely, the inherent noise (e.g., random measurement noise and temperature dependent bias) yields to imprecise motion-model based pose results. On one hand, drift is generated during data processing, on the other hand, the uncertain parameters of the physical system, moreover, the uncertainties induced by the environment of the robot (e.g., uneven, and slippery terrain [3,7]) significantly reduce the estimation performance and thus the reliability of the so-called a priori estimate.…”
Section: Methodsmentioning
confidence: 99%
“…However, the incorporated sensors are imperfect, namely, the inherent noise (e.g., random measurement noise and temperature dependent bias) yields to imprecise motion-model based pose results. On one hand, drift is generated during data processing, on the other hand, the uncertain parameters of the physical system, moreover, the uncertainties induced by the environment of the robot (e.g., uneven, and slippery terrain [3,7]) significantly reduce the estimation performance and thus the reliability of the so-called a priori estimate.…”
Section: Methodsmentioning
confidence: 99%
“…It is crucial to monitor and ensure the health conditions of an outdoor mobile robot and that its workspace terrain features are safe or at acceptable levels during its entire course of operation, as here the robot is exposed to undetected and uneven terrain features and adverse weather conditions, which causes an accelerated mode of system degradation resulting unexpected downtime, catastrophic failure, high maintenance cost, operational hazards, and customer dissatisfaction. The terrainability studies mentioned in [9][10][11][12][13][14] will help to plan paths, especially for last mail delivery or security robots, where the end destination or point-to-point travel can be executed with a suitable path planner, minimizing the traverse through unstructured terrain. However, such plans may need to be revised often as the terrain features may keep changing in an outdoor environment.…”
Section: Problem Statementmentioning
confidence: 99%
“…It is generally conducted by two approaches [8]: a wheel-terrain interactive vibration proprioceptive traversability analysis (retrospective techniques) and geometry or appearance-based exteroceptive analysis (prospective methods) using onboard sensors and adopting suitable Artificial Intelligence (AI) techniques for accurate classification. Some examples include terrain classification studies using an Inertial Measurement Unit (IMU) in [9,10], camerabased classification in [11], and a combination of camera and IMU-based classification in [12]. Similarly, a traversability analysis using 3D LiDAR is conducted in [13], and a comparative study showed better terrain classification under different lighting conditions using a 3D LiDAR sensor than a camera in [14].…”
Section: Introductionmentioning
confidence: 99%
“…An environmentindependent sensor selection for data acquisition and a fast and accurate classifier model is crucial for real-time CM frameworks for the outdoor environment. There are numerous AI-enabled and vibration-based terrainability studies for outdoor robots using different sensors to classify tile, stone, sand, asphalt, grass, and gravel [15][16][17][18][19], which will help to decide the traversability of the robot, but there is not a proper CM approach for assessing the health condition of the robot and level of terrain-induced concerns that accelerate system degradation. Hence, an automated CM and feasible remote controlling framework involving a shared autonomy and haptic feedback system is imperative for outdoor robots assisting in either stopping or minimising the exposure to extreme terrain conditions based on the internal health and external terrain states of the robot.…”
Section: Introductionmentioning
confidence: 99%